Legal Consequences of the Death of a Member of a Limited Liability Company: A Comparative Study of Positive Law and Islamic Law - Pris Firdaus, Alfian Muslim; Ulya, Zakiyatul; Mustofa, Imron (Syarah: Jurnal Hukum Islam dan Ekonomi, 2024)
A Limited Liability Company as a business entity that has a major role in improving the economy, must deal with something that it cannot control such as the death of one of the members of the Company. In this case, the law, becomes the last gate that strengthens the establishment of the Company. Positive law is a provision that applies in a country that often deviates from Islamic values. On the other hand, Islamic law is believed to contain better benefits than other laws. Positive and Islamic law have different provisions regarding the legal consequences of a member of a joint stock company dying. The purpose of this article is to analyze the similarities and differences in the provisions of the legal consequences of a Limited Liability Company because one of the members dies in the review of positive and Islamic law. The type of research conducted is a literature study with documentation as the data collection technique and comparative study as the analysis technique. The results of the study show that positive law and Islam according to the jumhur ulama have similarities in the legal consequences of the death of a member of the Limited Liability Company, which considers the Company to end immediately. The difference is that in positive law the company ends if it is agreed at the beginning of its establishment, except for the type of joint stock company. Meanwhile, according to the Maliki school of thought, the Company is not canceled even without an agreement at the beginning.